The Influence of Auditor Competence, Auditor Professional Ethics, and Auditor Independence on Internal Audit Quality - Salza Adzri Arismutia (Universitas Indonesia Membangun, 2026)
This study aims to analyze the influence of Auditor Competence, Auditor Professional Ethics, and Auditor Independence on Internal Audit Quality. This research is classified as quantitative research with a descriptive and verificative approach. Data collection techniques were obtained through field research, literature research, and questionnaire distribution to 130 respondents. The sampling technique used non-probability sampling with saturated sampling. Data analysis used multiple linear regression analysis and moderating regression analysis with data processing using IBM SPSS 26. The results showed that in the partial t-test, it was found that (1) Auditor Competence has a positive and significant effect on Internal Audit Quality, (2) Auditor Professional Ethics has a positive and significant effect on Internal Audit Quality, (3) Auditor Independence has no positive effect on Internal Audit Quality. Meanwhile, the simultaneous F-test results showed that Auditor Competence, Auditor Professional Ethics, and Auditor Independence simultaneously influence Internal Audit Quality. Furthermore, the coefficient of determination test results indicated that Auditor Competence, Auditor Professional Ethics, and Auditor Independence simultaneously influence Internal Audit Quality by 85.4%.